Transfer of sediment-derived carbon into blackworm (Lumbriculus variegatus) and crucian carp (Carassius carassius): Implications for 14C biosphere assessment in freshwater ecosystems - Soroush Majlesi; Sayed Tariq Uzzaman; Zahra Shirani; Jaakko Haverinen; Ari T.K. Ikonen; Jarkko Akkanen (Ecotoxicology and Environmental Safety, 2025)
Radiocarbon (14C) is known as one of the important radionuclides that can be released into the biosphere from the nuclear fuel cycle and radioactive waste repositories. It has a long half-life and can be distributed into aquatic environments as dissolved and gaseous species. To better understand its behavior in food webs, we simulated a freshwater food chain in a microcosm to investigate the contribution of sediment-derived C in freshwater animals. The natural abundance of 14C was used to estimate the contribution of sediment-derived C. The 14C/total carbon ratio in the sediment was highly depleted and thus ideal for partitioning C sources between sediment and food. An isotope mixing model was applied to estimate the proportion of sediment-derived C in the selected animals. The isotopic abundance of 15N was also used to further identify trophic levels in the animals. The findings revealed a significant contribution of sediment-derived C in blackworms (70–80 %), while only a small fraction was observed in the crucian carp (1–5 %). The findings identified sediment and fish food as the primary sources of C for worms and fish, respectively. Notably, the relative contribution of sediment-derived C was modulated by food availability. Specifically, uptake of sediment-derived C was higher in both species under conditions of limited food availability, and in fish when blackworms were absent. The findings may suggest higher uptake and potential radiological risks from sediment 14C in animals within brown food chains, particularly in overcrowded lakes with intense competition and during cold seasons when food is more limited.